Efek Samping Lama Aplikasi dari Bleaching Agent Hidrogen Peroksida 40% Terhadap Kekasaran Permukaan Resin Komposit Tipe Nanofill - Izfan Yulviansyah; Widjijono Widjijono; Dyah Irnawati (Jurnal Material Kedokteran Gigi, 2013)
Bleaching is a dental treatment chemically on the vital and non vital teeth undergoing discoloration. One technique is in office bleaching. Application of bleaching agent is not only touching the healthy tooth tissue, but also potentially touched restorative nanofill dental composite resins. Materials research is resin composite nanofil (Filtek Z350, 3 m, USA) and the bleaching agent 40% hydrogen peroxide (Opalescense Boost, USA). Disc-shaped sample (diameter 10 mm, thickness 2 mm) as many as 12 samples and divided into 3 groups each sample 4. The samples applied with bleaching agent 40% hydrogen peroxide at room temperatures (25 C) and contact time: 30 minutes, 45 minutes, and 60 minutes. Surface roughness was measured before and after application of bleaching. Surface roughness was measured before and after application of bleaching. Statistical analysis using a one way ANOVA and LSD 0,05. The results showed the average delta composite resin nanofil roughness with time sequential contacts 30, 45 and 60 minutes is 0,040 0,016 µm ± 0,045 µm ± 0.025, and 0.025 ± 0.125 µm. ANOVA test showed that there is a sinificant influence of variation of long application of hydrogen peroxide 40% against a nanofill composite resin surface roughness (p< 0.05). Test LSD indicates there is a significant difference between the delta’s average surface roughness on all groups, except the group of 30 and 45 minutes. Conclusion this research is a variation time contacts of 40% hydrogen peroxide application increases the surface roughness of a composite resin nanofil.